Formulation and evaluation of microspheres containing ropinirole hydrochloride using biodegradable polymers - Madan, Jyotsana R.; Kadam, Vinod; Bandavane, Sudarshan; Dua, Kamal (Asian Journal of Pharmaceutics (AJP), 2014)
The present work relates with developing long acting sustain release microspheres of ropinirole hydrochloride (RPN) for treatment of Parkinsonâ€™s disease, that will sustain drug release up to 1 month. Biodegradable microspheres of RPN were prepared by using two different polymers (poly lactic co glycolic acid [PLGA] 50:50 and PLGA 75:25) employing double emulsion (W/O/W) solvent evaporation method. Preliminary optimization of process parameter was done for concentration of polyvinyl alcohol (PVA) solution, stirring speed, temperature of PVA solution, ratio of the drug to polymer (D/P) and ratio of internal phase to external phase volume (IP/EP). All formulations were evaluated for particle size, percentage yield, entrapment efficiency (EE), shape etc. Formulation E3 and E4 shows maximum EE. % in vitro drug release per day of E3 and E4 batch was studied. The RPN was incorporated successfully in microspheres prepared with 0.5% w/v PVA at 8000 RPM stirring speed, 20Â°C processing temperature, 1:4 drug polymer ratio and 1:30 IP/EP ratio, which provides sustained release up to 4 weeks with better efficacy and patient compliance and can be employed as an alternative to existing oral medications. Key words: Entrapment efficiency, poly lactic co glycolic acid 50:50, polyvinyl alcohol, solvent evaporation, sustained release